Revealing the asymmetric redox dynamics of a porous bismuth anode in an efficient Ni//Bi battery. Issue 39 (5th October 2021) - Peng, Ming; Lu, Ying-Rui; Jiang, Yao; Lan, Jiao; Zhang, Yanlong; Chan, Ting-Shan; Tan, Yongwen
Abstract : A porous Bi electrode prepared by a chemical dealloying method shows asymmetric redox dynamics and contributes to an efficient Ni//Bi battery with high specific capacity, excellent rating performance and cycling stability. Abstract : As a promising energy technology, the rechargeable aqueous Ni//Bi battery is attracting increasing attention. However, a suitable Bi electrode with high capacity remains elusive and its redox dynamics remain to be uncovered. Here, we report a porous metallic Bi electrode for an efficient Ni//Bi battery by the chemical dealloying method. The as-prepared porous Bi electrode delivers a capacity of 9.43 mA h cm −2 (155.8 mA h g −1 ) at 10 mA cm −2, with significantly improved interface charge exchange and outstanding electrochemical response compared with a bulk Bi electrode. An Ni//Bi battery based on the self-standing anode achieves an ultrahigh high area specific capacity of 5.72 mA h cm −2 with specific energy density of 4.70 mW h cm −2 . Operando X-ray absorption spectroscopy, semi- operando X-ray photoelectron spectroscopy and Raman spectroscopy uncover the asymmetric redox dynamics of the Bi electrode. The present work highlights the importance of both intrinsic material properties and structural design, and will inspire more designs for high-performance electrodes of energy devices.